Potential Effects of Japanese Nuclear Waste in Fukushima on Fish Organs in the Sea of Japan - Tyas, Firda Ayuning; Riska Yulistiani (Jurnal Agricultural Science, 2023)
This research aims to investigate the effects of Fukushima nuclear waste on fish organs in the Japanese sea, particularly concerning the relationship between pollution levels and their impact on marine organisms. Through a scientific literature analysis, the findings indicate a positive correlation between contamination levels and the accumulation of radioactive compounds in fish organs. Marine organisms, especially those exposed to high contamination levels, tend to experience adverse effects on vital organs such as the liver, kidneys, and gills. The radiation's impact poses a high risk to the marine environment, especially for organisms at higher trophic levels with a greater potential for contamination. Beyond ecological impacts, this also affects economic and social aspects, posing threats to the fishing industry and the well-being of communities. The study underscores the need for international cooperation in addressing cross-border challenges posed by nuclear waste and calls for further research to deepen our understanding of the impacts and determinants involved. Overall, this research makes a significant contribution to efforts to protect the marine environment and sustain marine ecosystems amidst global challenges associated with nuclear activities